Search for novel proteolytic enzymes aimed at textile and agro-industrial applications: An overview of current and novel approaches - Queiroga, A. Catarina; Pintado, Manuela E.; Malcata, F. Xavier (Biocatalysis and biotransformation, 2012)
The types and sources of proteolytic enzymes, enzyme assays, strategies for fermentation yield improvement, and novel proteases and their applications in industrial sectors are widely covered in this review. We give a special focus on alkaline proteases for the textile and detergent industries, as well as for the degradation of keratin-rich wastes.